Influencia de la disfuncionalidad familiar en las conductas agresivas de los niños de la escuela Ramos de Oliva Echeverria de la ciudad de Machala, provincia de El Oro periodo 2013-2014. - Granda Catute, Liliana Ingrid (2014)
This research was conducted in school, "Ramos Echeverria Oliva" in the city of Machala. The research population were children, parent and teacher. The interest of our research on the influence of family dysfunction aggressive behavior is due to the great concern of the educational community antre conflicts are reflected in the classroom among students.